Comparative Studies of Coagulative and Fibrinolytic Faculties between the Japanese Monkey and the Human - Suzuki, K; Egawa, H; Hashimoto, S (Thrombosis and Haemostasis, 1977)
In the present study, the coagulative and the fibrinolytic faculties of the Japanese monkey (Macaca fuscata) were investigated and compared with those of the human.Regarding the coagulative faculty, the plasmic fibrinogen level, prothrombin times, and partial thromboplastin times of the Japanese monkey were similar to those of the human, but the antithrombin level in the monkey was higher than that in the human.Regarding the fibrinolytic faculty, the simian plasminogen level was significantly higher than the human, but the simian, plasma clot and the euglobulin clot lysis times were extremely prolonged, which means that the Japanese monkey has a great fibrinolytic potential, but that it is difficult to activate.In addition, the human and simian reactivities of plasminogen to streptokinase were also investigated and compared.